Donor NK and T Cells in the Periphery of Lung Transplant Recipients Contain High Frequencies of Killer Cell Immunoglobulin-Like Receptor-Positive Subsets - Hitz, Anna-Maria; Bläsing, Kim-Alina; Wiegmann, Bettina; Bellmàs-Sanz, Ramon; Chichelnitskiy, Evgeny; Wandrer, Franziska; Horn, Lisa-Marie; Neudörfl, Christine; Keil, Jana; Beushausen, Kerstin; Ius, Fabio; Sommer, Wiebke; et al. (Frontiers in Immunology, 2021)
Introduction For end-stage lung diseases, double lung transplantation (DLTx) is the ultimate curative treatment option. However, acute and chronic rejection and chronic dysfunction are major limitations in thoracic transplantation medicine. Thus, a better understanding of the contribution of immune responses early after DLTx is urgently needed. Passenger cells, derived from donor lungs and migrating into the recipient periphery, are comprised primarily by NK and T cells. Here, we aimed at characterizing the expression of killer cell immunoglobulin-like receptors (KIR) on donor and recipient NK and T cells in recipient blood after DLTx. Furthermore, we investigated the functional status and capacity of donor vs. recipient NK cells. Methods Peripheral blood samples of 51 DLTx recipients were analyzed pre Tx and at T0, T24 and 3wk post Tx for the presence of HLA-mismatched donor NK and T cells, their KIR repertoire as well as activation status using flow cytometry. Results Within the first 3 weeks after DLTx, donor NK and T cells were detected in all patients with a peak at T0. An increase of the KIR2DL/S1-positive subset was found within the donor NK cell repertoire. Moreover, donor NK cells showed significantly higher frequencies of KIR2DL/S1-positive cells (p<0.01) 3wk post DLTx compared to recipient NK cells. This effect was also observed in donor KIR+ T cells 3wk after DLTx with higher proportions of KIR2DL/S1 (p<0.05) and KIR3DL/S1 (p<0.01) positive T cells. Higher activation levels of donor NK and T cells (p<0.001) were detected compared to recipient cells via CD25 expression as well as a higher degranulation capacity upon activation by K562 target cells. Conclusion Higher frequencies of donor NK and T cells expressing KIR compared to recipient NK and T cells argue for their origin in the lung as a part of a highly specialized immunocompetent compartment. Despite KIR expression, higher activation levels of donor NK and T cells in the periphery of recipients suggest their pre-activation during the ex situ phase. Taken together, donor NK and T cells are likely to have a regulatory effect in the balance between tolerance and rejection and, hence, graft survival after DLTx.